2021
DOI: 10.1037/trm0000276
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the impact of trauma-informed education programs on academic and academic-related functioning for students who have experienced childhood adversity.

Abstract: The purpose of this study was to conduct a systematic review of the existing literature regarding trauma-informed education programs and their impact on academic and academic-related outcomes. The articles included for review (n = 15) contained data on trauma-informed education programs implemented in preschool, primary/elementary, and high school settings. Academic and academic-related outcomes reported included attendance, disciplinary referrals, suspension, and academic achievement, as well as student resil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Considering the effects of negative reactions to trauma disclosure, many participants suggested that it would be important to educate both children and parents about mental health difficulties and trauma in childhood. Trauma-focused education programs in schools have achieved promising results in terms of academic-related outcomes (e.g., attendance and academic achievement) (Roseby & Gascoigne, 2021). Future interventions could consider the idea of training teachers in recognising traumatic symptoms in children, and schools could be used as locations to facilitate informative meetings to share information with parents about trauma and coping strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the effects of negative reactions to trauma disclosure, many participants suggested that it would be important to educate both children and parents about mental health difficulties and trauma in childhood. Trauma-focused education programs in schools have achieved promising results in terms of academic-related outcomes (e.g., attendance and academic achievement) (Roseby & Gascoigne, 2021). Future interventions could consider the idea of training teachers in recognising traumatic symptoms in children, and schools could be used as locations to facilitate informative meetings to share information with parents about trauma and coping strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to common premises underlying the zero tolerance and school safety discourse, the interviews clearly demonstrate that an explanation that focuses only on the pathology of the child is unsatisfactory and that a young persons’ problematic behaviour, eventually leading to their suspension does not occur in a vacuum (Caslin, 2021). To better understand young persons’ behaviour and to deal with it effectively, the circumstances that led to its development and the context in which it occurs must be considered (Roseby & Gascoigne, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular relevance to the current investigation is the strong emphasis on shifting educators' perspectives from viewing students' undesirable behaviour as inherently bad or oppositional toward viewing each student as having been affected in some way by their experiences (Woodbridge et al, 2016). A growing body of evidence points to the positive effects of trauma-informed programs on children exposed to early adversity (Roseby & Gascoigne, 2021), including reductions in suspension rates (Millenky et al, 2019).…”
Section: Conclusion and Pr Actical Implicationsmentioning
confidence: 99%
“…In these recent reviews, only a small number 10.3389/feduc.2022.1005887 of studies on trauma-informed schools PD were identified. Roseby and Gascoigne (2021) identified the most studies, but these spanned preschool, elementary, and high school settings. It is likely that unique considerations at each level (e.g., high school teachers having a larger number of students who rotate classes) affect how trauma-informed PD is put into practice, necessitating an accumulation of evidence at each level.…”
Section: Existing Research On Trauma-informed Professional Developmen...mentioning
confidence: 99%